Colposcopy: Gynecological vision in viewing oral lesions - Abhishek Singh Nayyar; Mubeen Khan; U D Bafna; Ahmed Siddique; H C Gayitri (Wolters Kluwer Medknow Publications, 2014)
Context: The diagnosis of malignant and potentially malignant epithelial lesions of the oral mucosa cannot be based solely on clinical findings. The histologic evaluation of a representative biopsy specimen thus becomes necessary. The site for biopsy however is always a subjective choice that sometimes raises doubts about its representativeness. So far, no simple and reliable method is available for the selection of the most appropriate area for biopsy. Colposcopy is helpful in the selection of these sites of epithelial dysplasia depending upon the vascular patterns. Aims: This study was planned to assess the role of Colposcopic examination in the selection of biopsy site in patients with varying grades of oral epithelial dysplasia at various sites. Settings and Design: One hundred and eighty patients between the ages of 30 and 60 years clinically diagnosed with leukoplakia and carcinoma buccal mucosa were included in the study. Materials and Methods: For each of the subjects, a thorough clinical examination followed by Colposcopic assessment was carried out for the selection of biopsy site from the involved mucosa. The histopathological findings were then compared in the two cases and results analyzed. Statistical Analysis Used: The statistical analysis was performed using a paired t-test. Results: In our study, sensitivity and specificity for the selection of biopsy site by Colposcopic examination was found to be higher for leukoplakia than for carcinoma buccal mucosa. Conclusions: It was concluded that Colposcopic examination was found to be significant in the selection of biopsy site for leukoplakia while clinical criterion was found to be more appropriate for carcinoma buccal mucosa cases.